Looking behind the curtain: quantifying massive shark mortality in fish aggregating devices. Issue 6 (8th August 2013) - Filmalter, John David; Capello, Manuela; Deneubourg, Jean-Louis; Cowley, Paul Denfer; Dagorn, Laurent
Abstract : Increasing catch rates are considered the main impact of dynamic fisheries practices on marine ecosystems, but other effects can be equally important and are often ignored. Here we quantify a major, previously unknown source of shark mortality: entanglement in drifting fish aggregating devices, now widely used in the global tropical tuna purse‐seine fishery. Using satellite tagging and underwater observational data, we developed two novel, independent, and complementary approaches, which quantify and highlight the scale of this problem. Entanglement mortality of silky sharks (Carcharhinus falciformis ) in the Indian Ocean was 5–10 times that of the known bycatch of this imperiled species from the region's purse‐seine fleet. More importantly, these estimates from a single ocean (480 000–960 000 silky sharks) mirror those from all world fisheries combined (400 000–2 million silky sharks), a situation that clearly requires immediate management intervention and extensive monitoring.